MacroH2A1 Immunoexpression in Breast Cancer - Broggi, Giuseppe; Filetti, Veronica; Ieni, Antonio; Rapisarda, Venerando; Ledda, Caterina; Vitale, Ermanno; Varricchio, Silvia; Russo, Daniela; Lombardo, Claudia; Tuccari, Giovanni; Caltabiano, Rosario; Loreto, Carla (Frontiers in Oncology, 2020)
MacroH2A1 has two splice isoforms, macroH2A1.1 and macroH2A1.2, that have been studied in several form of cancer. In the literature there are not many scientific papers dealing with the role of macroH2A1 in breast cancer. Breast cancer is the most frequent form of malignancy in females. It tend to metastasize to the bone in approximately 70% of patients. Despite treatment, new bone metastases will still occur in 30%-50% of cases with advanced disease. Overall 5-year survival after the diagnosis of bone metastasis is approximately 20%. Osteoclasts and osteoblasts of the bone microenvironment are engaged by soluble factors released by neoplastic cells, resulting in bone matrix breakdown. This malfunction enhances the proliferation of the cancer cells, creating a vicious cycle. We investigated immunohistochemical expression of macroH2A1 in primitive breast cancer, focusing on the comparison of metastatic and non-metastatic cases. Furthermore, the immunohistochemical expression of macroH2A1 has been evaluated both in all cases of nodal metastases and in distant metastases. Our data demonstrated that macroH2A1 expression was higher expressed in metastatic breast cancer (77%) vs. non-metastatic breast cancer (32%). Also in analyzed metastases cases, a high macroH2A1 expression was detected: 85% and 80% in nodal and distant metastases cases, respectively. These results supported the fact that macroH2A1 is more highly expressed in breast cancer with worst prognosis.